THE URGENCY OF CENTRAL BANK DIGITAL CURRENCY (CBDC) IMPLEMENTATION; MAQĀSHĪD SYARĪ’AH PERSPECTIVE - Firdiansyah, Fitra Azkiya (UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This study examines the urgency of the Central Bank Digital Currency (CBDC) with a maqashid Syariah perspective. The challenges of digital transactions have forced people to use cryptocurrencies without the use of asset assignments so that they have a big risk, this makes them illegal, while electronic money has not answered the challenges of digital transactions. The methodology used in writing this article is a descriptive qualitative method with a normative approach to analysis on maslahah and mafsadah contained in Maqashid sharia. The data used by the author is secondary data. The results of the study can be concluded that the implementation of Central Bank Digital Currency (CBDC) will provide more maslahah than mafsadah, while cryptocurrencies are currently widely traded freely by the Muslim community in general even though they are considered haram and illegal. This shows that the Central Bank Digital Currency (CBDC) has the urgency of its use in the economic practice of Muslims in general, with the same form but eliminating the bad elements contained in cryptocurrency, enforcing Islamic sharia, and saving the economy of the Muslim community according to Maqashid. sharia